Bone height and width evaluation before dental implant placement on panoramic radiographs: a scoping review - Asmarani, Shely Levita; Azhari, Azhari; Pramanik, Farina (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2022)
Objectives: The aim of this study is to evaluate the bone height and its width on panoramic radiography prior to dental implant placement. Review: This study was carried out using scoping review methods. The referenced articles were published between 2010-2021 in English or Indonesian. The search was performed using PubMed and PMC database with keywords “(((Evaluation) AND (Presurgical)) AND (Dental Implant)) AND (Radiograph)) AND (Panoramic)” and Science Direct with keywords "presurgical evaluation dental implant in panoramic radiograph". Preferred Reporting Items for Systematic Review and Meta-analysis Scoping Review (PRISMA-Scr) was utilized to perform the article finding process. It is found that the height of alveolar bone after being assessed by panoramic radiograph is between 7.95-23.42 mm while the alveolar bone width is between 7.04-10.41 mm. Conclusion: Panoramic radiograph can be performed to evaluate bone height and width before the dental implant placement procedure.